Spatial Pattern of Genetic Diversity in the Blood Fluke Aporocotyle argentinensis (Digenea, Aporocotylidae) from South American Hakes (Pisces: Merluccidae) - Oliva, Marcelo E.; Cárdenas, Leyla; Valdivia, Isabel M.; Bruning, Paulina; Figueroa-Fabrega, Luis; Escribano, Rubén (My University, 2022)
Distribution of blood fluke Aporocotyle spp. parasitizing Merluccius species from the coasts of South America (Peru, Chile and Argentina) constitutes an excellent opportunity to evaluate the geographical amplitude in which a parasite can exploit the same host species. Phylogenetic analyses (partial sequences of SSU rDNA, LSU rDNa, and cox1 gene) were performed to characterize the genetic lineage of Aporocotyle species described from South American Hake: Merluccius australis, M. gayi, and M. hubbsi. The Phylogenetic analyses (SSUrDNA and LSUrDNA) revealed an absence of genetic variability in Aporocotyle obtained over a gradient of 6800 km, covering two oceans and three closely related hosts. Consequently, the species infecting Merluccius spp. in South America is Aporocotyle argentinensis Smith 1969, by priority law. Phylogeographic analysis suggests a pattern of spatial differentiation and genetic population structure associated with the geographical distribution of the host’s species. A specimen with a haplotype found in M. gayi was collected from M. australis from Puerto Montt, and three worms (from Coquimbo, Constitución and Talcahuano, host M. gayi) harbored a haplotype found in M. australis + M. hubbsi, suggesting that the gene flow between different hosts and geographical distributions occurs when the distribution of adequate hosts overlaps, avoiding speciation in blood flukes from South American hakes.
Keywords: Phylogeography; Genetic lineage; SSU rDNA gene; LSU rDNA gene; Cox1 gene; Spatial differentiation; Genetic population structure; Host induced variability